GUIDELINES FOR THE DEVELOPMENT OF ACTIVE LEARNING MANAGEMENT IN SMALL-SIZED SCHOOLS UNDER THE OFFICE OF CHIANG RAI PRIMARY EDUCATIONAL SERVICE AREA 3 - Mukdasawan, Wasana; Jatuporn, Watchara (Journal of Educational Review Faculty of Education in MCU, 2026)
This research aimed to: 1) study the current and desirable conditions of active learning management, 2) examine the priority needs for developing active learning management, and 3) explore the guidelines for developing active learning management in small-sized schools under the Chiang Rai Primary Educational Service Area Office 3. This study employed a mixed-methods research design. The sample consisted of 186 school administrators and teachers from small-sized schools, selected through stratified random sampling, and 5 experts selected by purposive sampling. The research instruments included a questionnaire on the current and desirable conditions of active learning management and an interview form on the guidelines for developing active learning management. Data were analyzed using descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as the modified Priority Needs Index (PNImodified) and content analysis. The findings revealed that 1) the overall current and desirable conditions of active learning management in small-sized schools were at a high level, 2) the priority needs for developing active learning management indicated that the aspect of organizing active learning activities had the highest Priority Needs Index, followed by measurement and evaluation and learner-centered approaches, while the aspect of activity design had the lowest, and 3) the guidelines for developing active learning management in small-sized schools under the Chiang Rai Primary Educational Service Area Office 3 consisted of five approaches and fifteen implementation methods.